2012
DOI: 10.5194/angeo-30-1107-2012
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal analysis of interplanetary magnetic field obtained during CME events

Abstract: Abstract. In this paper, we have analyzed the interplanetary magnetic field (IMF) obtained by ACE satellite during the coronal mass ejection events. The characterization of the IMF fluctuations was performed using the singular power spectra deviations obtained from a wavelet transform modulus maxima (WTMM) approach. The results suggest the existence of different multifractal processes driving the intermittency during and after the CME events on the IMF time series. The characteristic time scales found, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We used the cross-wavelet transform to obtain the common periods between two time series and, also, to study the temporal variability of the main periods found (Bolzan et al, 2012). The XWT is given by (Grinsted et al, 2004)…”
Section: Cross-wavelet Analysismentioning
confidence: 99%
“…We used the cross-wavelet transform to obtain the common periods between two time series and, also, to study the temporal variability of the main periods found (Bolzan et al, 2012). The XWT is given by (Grinsted et al, 2004)…”
Section: Cross-wavelet Analysismentioning
confidence: 99%
“…where a is the scaling factor and W XY the cross-wavelet transform applied in two time series given by (Torrence and Compo, 1998;Bolzan and Vieira, 2006)…”
Section: Cross-wavelet Analysismentioning
confidence: 99%
“…According to previous works (Bolzan et al, 2009a, b;Bolzan and Rosa, 2012), the vertical total electron content (VTEC) time series have very intermittent characteristics, mainly at small scales. In addition, the VTEC time series depend on geomagnetic substorm and storm activities.…”
Section: Introductionmentioning
confidence: 94%
“…This process provides the power-law for small α the scaling exponents τ (q) -the multifractal spectrum (Muzy et al, 1991). Arneodo et al (1995) used a hierarchy of the WTMM to obtain the partition function Z(a, q) based on the multifractal formalism.…”
Section: Multifractal Analysismentioning
confidence: 99%
See 1 more Smart Citation